Peran Masyarakat Berbasis Agama dalam Mewujudkan Anggaran Daerah â€œPro Poorâ€ Sebagai Upaya Pengentasan Kemiskinan Di Kabupaten Bintan - Alfiandri, Alfiandri; Wahyuni, Sri (Jurnal Ilmu Administrasi Negara (JUAN), 2018)
The local annual budget (APBD) is one of the instruments of government policy to finance development programs, services and empowerment in the area. Budgets are formulated by local governments and legislators to advance aspiration developed in the society. Nevertheless, the budget policy area always biased interests, both political interests and the interests of local control of resources. Therefore, the community can play a role in determining the area of pro-poor budget for poverty alleviation efforts in the area. Faith-based societies, including in the civil society organizations that play a role in achieving pro-poor local budgets. This study is intended to look at the role, which the researchers analyzed the role of faith-based communities in achieving pro-poor local budgets in an effort to alleviate poverty in Bintan regency. To achieve these objectives, this study used a qualitative approach. This approach is very relevant to see and map the role of faith-based communities in achieving pro-poor local budgets. This study concluded that the role of faith-based communities have not been effective in achieving pro-poor local budgets. This is due to a lack of faith-based public awareness of the role and responsibilities, lack of institutional and managerial faith-based community organization and lack of socialization of the government.